Concept Image Siswa dalam Materi Barisan dan Deret pada Pembelajaran Berdiferensiasi - Dita Oktavihari; Junaidi Junaidi; Gilang Primajati; M. Gunawan Supiarmo; Eka Kurniawan; Alvano Tugas Hendrawan (Mandalika Mathematics and Educations Journal, 2025)
This study aims to describe students' concept images on sequences and series in differentiated learning and to examine the concept image gap between students, teachers, and mathematicians. This study used a qualitative approach with a didactic design and a hermeneutic phenomenology method. The research subjects included students, teachers, and mathematicians, who were selected purposively. Data were collected through learning observations, questionnaires, and in-depth interviews, and then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results showed that students' conceptual images of sequences and series were dominated by intuitive, visual, and procedural understandings. Students were able to recognize real-world patterns and contexts, but tended to rely on repeated addition or multiplication rather than using formal definitions and symbolic formulas. In geometric sequences and series, a concept image conflict was found due to students' difficulty in understanding exponential growth patterns. Although differentiated learning provides space for diverse student learning styles, the results show that this approach does not fully guarantee the formation of a complete formal conceptual understanding. Therefore, strengthening conceptual scaffolding is needed so that students' concept images are more aligned with the correct concept definition. Penelitian ini bertujuan untuk mendeskripsikan concept image siswa pada materi barisan dan deret dalam pembelajaran berdiferensiasi serta mengkaji kesenjangan concept image antara siswa, guru, dan matematikawan. Penelitian ini menggunakan pendekatan kualitatif dengan desain didaktis dan metode fenomenologi hermeneutik. Subjek penelitian meliputi siswa, guru, dan matematikawan, yang dipilih secara purposif. Pengumpulan data dilakukan melalui observasi pembelajaran, kuesioner, serta wawancara mendalam, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa concept image siswa pada materi barisan dan deret didominasi oleh pemahaman intuitif, visual, dan prosedural. Siswa mampu mengenali pola dan konteks nyata, namun cenderung mengandalkan penjumlahan atau perkalian berulang dibandingkan penggunaan definisi formal dan rumus simbolik. Pada barisan dan deret geometri, ditemukan conflict concept image akibat kesulitan siswa dalam memahami pola pertumbuhan eksponensial. Meskipun pembelajaran berdiferensiasi memberikan ruang bagi keberagaman cara belajar siswa, hasil penelitian menunjukkan bahwa pendekatan ini belum sepenuhnya menjamin terbentuknya pemahaman konseptual formal yang utuh. Oleh karena itu, diperlukan penguatan scaffolding konseptual agar concept image siswa lebih selaras dengan concept definition yang benar.